To add 4(g-2) + (g+2), we can first distribute the 4 to the terms in the parentheses:
4(g-2) + (g+2) = 4g - 8 + g + 2
Now we can combine like terms:
4g - 8 + g + 2 = (4g + g) + (-8 + 2) = 5g - 6
So the simplified expression is 5g - 6.
Use the properties of operations to add 4(g−2)+(g+2) .
8 answers
Use the properties of operations to subtract (h+k)−(2k−h) .
To subtract (h+k) - (2k - h), we can distribute the negative sign to each term inside the second parentheses:
(h + k) - (2k - h) = (h + k) - 2k + h
Now we can combine like terms:
(h + k) - 2k + h = h + h + k - 2k = 2h + k - 2k
Finally, we can combine like terms again:
2h + k - 2k = 2h + (k - 2k) = 2h - k
So the simplified expression is 2h - k.
(h + k) - (2k - h) = (h + k) - 2k + h
Now we can combine like terms:
(h + k) - 2k + h = h + h + k - 2k = 2h + k - 2k
Finally, we can combine like terms again:
2h + k - 2k = 2h + (k - 2k) = 2h - k
So the simplified expression is 2h - k.
Use the properties of operations to subtract (p−3)−(2.4+2p)
To subtract (p-3) - (2.4 + 2p), we can distribute the negative sign to each term inside the second parentheses:
(p - 3) - (2.4 + 2p) = p - 3 - 2.4 - 2p
Now we can combine like terms:
p - 3 - 2.4 - 2p = (p - 2p) + (-3 - 2.4) = -p + (-5.4)
So the simplified expression is -p - 5.4.
(p - 3) - (2.4 + 2p) = p - 3 - 2.4 - 2p
Now we can combine like terms:
p - 3 - 2.4 - 2p = (p - 2p) + (-3 - 2.4) = -p + (-5.4)
So the simplified expression is -p - 5.4.
Subtract: 2(k−4)−3(2k−1) .
To subtract 2(k-4) - 3(2k-1), we can apply the distributive property to each term:
2(k-4) - 3(2k-1) = 2k - 8 - (6k - 3)
Now, we can remove the parentheses and combine like terms:
2k - 8 - 6k + 3 = (2k - 6k) + (-8 + 3) = -4k - 5
So, the simplified expression is -4k - 5.
2(k-4) - 3(2k-1) = 2k - 8 - (6k - 3)
Now, we can remove the parentheses and combine like terms:
2k - 8 - 6k + 3 = (2k - 6k) + (-8 + 3) = -4k - 5
So, the simplified expression is -4k - 5.
all of these answers are correct for connections academy as far as i know